Mini-Clonal Technology-An Innovative Mass Multiplication Technology for Tree species - Parthiban, K .T.; Kumar, N. Krishna; Fernandaz, C. Cinthia (Indian Forester, 2021)
The growing importance on promotion of plantation and agroforestry in India demands production of quality planting materials to satisfy the demands of tree growing farmers and wood based industries. The National Forest and Agroforestry policies also prioritized ensuring quality seedling production for successful establishment of forestry and agroforestry plantations. As of now, most plantation activities in the country are carried out through seed based seedling production barring few exceptions which exhibited wide variations in growth, yield, productivity and adoptability. Under such circumstances, The Forest College and Research Institute (TNAU) has developed species specific mini clonal technology for wide range of pulpwood, plywood and timber species viz., Eucalyptus, Casuarina, Melia, Teak, African Mahagony, Toon and Kadam. This innovative mass multiplication technology exhibits greater potential of adoption across regions towards mass multiplication of wide range of species and to ensure quality seedling production as envisaged in National Agroforestry policy. The rapid multiplication coupled with increased rooting efficiency in a short duration and elimination of epigenetic variation attracts this technology as a most promising in forestry and agroforestry plantation development program.